Evaluasi Program Bantuan Operasional Sekolah Di Sekolah Dasar Negeri 004 Tanjung Palas, Kabupaten Bulungan - Dewi Ayu Pratiwi; Imam Muazansyah (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2021)
This study aims to evaluate the School Operational Grant Program (BOS) at SD Negeri 004 Tanjung Palas by using a descriptive qualitative research approach method, namely the researcher tries to explain the real picture related to the evaluation of the school operational assistance program (boss) at SD Negeri 004 Tanjung Palas. To obtain comprehensive data, observation, documentation, and in-depth interviews were conducted with informants as primary data sources. and secondary data, including processed data or officially, published data obtained from media news, literature, previous research articles, documentation, and archives of BOS funds in this study. Analysis of the research data, namely: data reduction, data presentation, and concluding / verification. The results of the study can be described that the use of School Operational Grant funds at SD Negeri 004 Tanjung Palas cannot be categorized as good as can be seen specifically in the indicators of program evaluation criteria used, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. In this case, two indicators have not been assessed for optimal implementation, namely in terms of effectiveness because schools do not prioritize student needs while focusing more on school support equipment, and in terms of equity, it cannot be said to be good because the provision of learning needs, namely text books cannot be felt by all students and must complement independently. This is an evaluation material for the school. Reporting on the use of BOS funds at the 004 Tanjung Palas Public Elementary School has been running well and based on the prescribed standard procedures, and also the monitoring process of the use of BOS funds in SD Negeri 004 Tanjung Palas so far can be categorized as good. Because the supervision uses a mechanism that applies and can involve many parties so that the results can be accounted for.